2018
DOI: 10.1002/lno.10809
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen availability on long‐distance electron transport in marine sediments

Abstract: Cable bacteria are long, multicellular, filamentous bacteria that can conduct electrons over centimeter distances in marine and freshwater sediments. Recent studies indicate that cable bacteria are widely present in many coastal environments, where they exert a major influence on the biogeochemistry of the sediment. Their energy metabolism can be based on the aerobic oxidation of sulfide, and hence to better understand their natural occurrence and distribution, we examined the growth and activity of cable bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…In 2017, the low bottom water O 2 concentration recorded at station E was sufficient to maintain cable (Table 1). Cable bacteria activity has been shown to decrease in response to decreasing O 2 concentrations (Burdorf et al, 2018). It is thus plausible that the relatively low densities found at stations D, E and F reflect an electron acceptor limitation, and that higher densities might be present during conditions of higher O 2 availability (e.g.…”
Section: Cable Bacteria In the Sediment Of The Egb Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, the low bottom water O 2 concentration recorded at station E was sufficient to maintain cable (Table 1). Cable bacteria activity has been shown to decrease in response to decreasing O 2 concentrations (Burdorf et al, 2018). It is thus plausible that the relatively low densities found at stations D, E and F reflect an electron acceptor limitation, and that higher densities might be present during conditions of higher O 2 availability (e.g.…”
Section: Cable Bacteria In the Sediment Of The Egb Basinmentioning
confidence: 99%
“…The in situ O 2 level recorded at station E in 2017 (≤ 5 μM) is the lowest so far reported for cable bacteria. Previously, cable bacteria have been reported at bottom water O 2 concentration as low as 100 μM(Seitaj et al, 2015), whereas laboratory sediment incubations have shown a lower O 2 limit of 50 μM(Burdorf et al, 2018).…”
mentioning
confidence: 97%
“…several centimetres depth provides cable bacteria a competitive advantage over other S-oxidising bacteria in aquatic environments (Meysman 2018). Cable bacteria have been documented in a range of fresh water (Risgaard-Petersen et al 2015;Müller et al 2016) and marine environments (Malkin et al 2014;Burdorf et al 2017), however, they appear to be particularly active in sediments overlain by seasonally hypoxic bottom waters (Seitaj et al 2015;Burdorf et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cable bacteria are suggested to thrive in coastal sediments characterised by high rates of H 2 S production due to high rates of organic matter mineralisation (Malkin et al 2014;Burdorf et al 2017;Hermans et al 2019a). Laboratory and model studies have shown that the dissolution of FeS accounts for 12 to 94% of the H 2 S consumed by cable bacteria, while the other source is H 2 S production from the reduction of SO 4 2- (Risgaard-Petersen et al 2012;Meysman et al 2015;Burdorf et al 2018). At present, it is not known if cable bacteria activity can establish in sediments that are relatively low in FeS and dissolved H 2 S.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] While nanometer-scale electron transport is known to occur in chloroplasts and mitochondria [11][12][13][14] , and micrometerscale electrical currents are induced in the nanowire appendages of metal-reducing bacteria [15][16][17] , the centimeter-scale electron transport by cable bacteria extends the known length scale of biological transport by several orders of magnitude. [2] While some aspects of the physiology and overall metabolism of cable bacteria have been recently resolved [18,19] , the mechanism of long-distance electron transport (LDET) inside cable bacteria remains elusive. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) have shown that the surface of cable bacteria has a unique topography, with parallel ridges running along the entire length of the filaments.…”
mentioning
confidence: 99%